Energy Efficiency: Determinants and Roles on Sustainable Development in Emerging Country - Tiep, Le Thanh; Huan, Ngo Quang; Hong, Tran Thi Thuy (International Journal of Energy Economics and Policy, 2021)
Energy efficiency (ENE) is a growing issue in emerging countries. This study aims to evaluate the impact of ENE on sustainable development (SDE). By this research, we have developed constructed variables that contribute to energy efficiency such as usage behavior (UBE), energy resources (ERE), construction design (CDE), appliances, equipment (AEQ), and maintenance (MCE). We use quantitative technique such as Smart PLS SEM to analyze the data of the small and medium size enterprises (SMEs) of Vietnam in the year 2020. The findings suggest a positive and significant impact of energy efficiency on sustainable development. This contribution has also confirmed the contribution of usage behavior (UBE), energy resources (ERE), construction design (CDE), appliances, equipment (AEQ), and maintenance (MCE) affecting to energy efficiency in emerging country. This study contributes to the literature of energy efficiency and sustainable development of SMEs in emerging country context. The outcomes of this study can be used by entrepreneurs, top management as an attempt to boost the performance of the SMEs in emerging markets by applying energy efficiency measures for sustainable development as a value-added contribution to this research. Keywords: Determinants of Energy Efficiency, Energy Efficiency, Renewable Energy, Sustainable Development, Emerging Country. JEL Classifications: Q21, Q25, Q43 DOI: https://doi.org/10.32479/ijeep.10717